The role of the pregnancy heart team in clinical practice - Lucà, Fabiana; Colivicchi, Furio; Parrini, Iris; Russo, Maria Giovanna; Di Fusco, Stefania Angela; Ceravolo, Roberto; Riccio, Carmine; Favilli, Silvia; Rossini, Roberta; Gelsomino, Sandro; Oliva, Fabrizio; Gulizia, Michele Massimo (Frontiers in Cardiovascular Medicine, 2023)
Significant maternal and fetal morbidity and mortality risk has been shown to be associated with cardiovascular disease in pregnancy. Several determinants, such as the increasing number of females with corrected congenital heart disease in reproductive age, a more advanced maternal age associated with cardiovascular risk factors, and a greater prevalence of preexisting comorbidities related to cardiac disorders such as cancer and COVID-19), lead to a higher incidence of cardiac complications in pregnancy in the last few decades. However, adopting a multidisciplinary strategy may influence maternal and neonatal outcomes. This review aims at assessing the role of the Pregnancy Heart Team, which should ensure careful pre-pregnancy counseling, pregnancy monitoring, and delivery planning for both congenital and other cardiac or metabolic disorders, addressing several emerging aspects in the multidisciplinary team-based approach.